Drone-Assisted Precision Fertilization in Shallot Cultivation: Cost-Efficiency Evaluation in Brebes Regency, Central Java - Gilang Prananda, Narendra (Politeknik Siber Cerdika Internasional, 2025)
Brebes Regency in Central Java, Indonesia, is recognized as the largest shallot production center nationally, contributing approximately 65% of provincial output. However, conventional fertilization methods face critical challenges including high operational costs, labor intensity, and uneven distribution patterns that compromise crop productivity. This study evaluates the cost-efficiency of implementing drone-assisted precision fertilization technology in shallot cultivation. A comparative field experiment was conducted across 20 hectares during the 2023-2024 growing season, contrasting drone-based application systems with traditional manual methods. Key performance indicators measured included operational costs per hectare, time efficiency, fertilizer distribution uniformity, labor requirements, and resultant crop yields. Results demonstrate that drone-based fertilization achieved a 28.3% reduction in operational costs (from 842/ha to 604/ha), a 73.5% decrease in labor hours (from 34 to 9 hours/ha), and a 35.7% improvement in fertilizer distribution uniformity coefficient (from 0.68 to 0.92). Furthermore, shallot productivity increased by 14.2% (from 11.8 to 13.5 tons/ha) under drone application. Economic analysis revealed a favorable benefit-cost ratio of 2.34 and a payback period of 2.3 years for drone technology adoption. Despite promising outcomes, implementation constraints include initial capital requirements, technical expertise demands, regulatory compliance, and terrain-specific operational limitations. This research provides empirical evidence supporting drone technology as a viable precision agriculture solution for enhancing cost-efficiency and productivity in Indonesian shallot cultivation systems.